STUDY MODULE „PROJECT WEEK“: THROUGH THE EYES OF STUDENTS (Innovation in Woodworking Industry and Engineering design, 2026)
Competition in the educational field today brought awareness of the need of change in the manner of teaching and knowledge acquisition. It is clear that the university, as an educational and scientific institution, should follow and answer the demands of society for highly qualified and self-confident young professionals. The University of Forestry in Sofia introduced a new study module, called Project Week, in the regular curriculum for Engineering Design Bachelor Program. The module aims at increasing the skills and competence of students and preparing them for their future professional career. The paper presents the results of our experience from the past two years from the students’ point of view. Inquiries were held with the participants, students of 3rd year of study. The authors of this paper put the accent on the expectations and results of this new form of teaching.The final results are an indicator of work done and give us the guidelines for future development towards improving the manner and conditions of work.